AKIBAT HUKUM PENCATATAN PERKAWINAN SIRI MENGGUNAKAN SURAT PERNYATAAN TANGGUNG JAWAB MUTLAK PADA KARTU KELUARGA DI KABUPATEN BANDUNG BARAT DITINJAU DARI HUKUM ISLAM BERDASARKAN UNDANG-UNDANG PERKAWINAN - Amirul Adli; Bambang Daru Nugroho; Hazar Kusmayanti (IAIN Bengkulu, 2022)
Abstract: There is a phenomenon where married husband and wife only fulfill the requirements and pillars of Islamic marriage. This marriage is called a siri marriage. The Directorate General of Population and Civil Registration states that every married Indonesian citizen is required to have a family card even if they are married outside of wedlock. This policy allows unregistered marriages to obtain a KK using the SPTJM form with a special note that the marriage is not registered. This study uses a normative juridical approach and analytical descriptive research specifications, namely by explaining the laws and regulations related to the events studied. in this case regarding the registration of unregistered marriages using SPTJM on KK. Based on the results of the study, the use of SPTJM against KK has no legal consequences, the use of SPTJM against KK has no legal consequences, the marriage that is carried out will legally result in the status of the child from the marriage being unclear, the rights and obligations of the husband and problems in managing marital assets are regulated in UUP and KHI.Keywords: KK, Siri Marriage, SPTJM